Valutazione comparativa di due metodi automatici per lo screening di Treponema pallidum - Fulvia Milano; Luigi Cianci; Micaela Pelagi; Loredana Pangaro; Giovanni Olivieri; Paola Verza; Gian Carlo Guazzotti (Microbiologia Medica, 2007)
In the present study we evaluated the performance of two automated chemiluminescence immunoassay for detection of Treponema pallidum antibodies in a routine laboratory approach. One hundred fifty samples, obtained from patients admitted to hospital with no signs or clinical history of syphilis were studied.All samples were tested for Treponema pallidum antibodies by the qualitative method Syphilis TP Architect (Abbott) and with DIASORIN Treponema Screen (DiaSorin) and the reactive results were confirmed by VDRL and IgM ELISA. Western blot IgG and IgM (AID GmbH),VDRL (Abbott) and EIAgen TMPA IgM (Adaltis) were used to analyze discrepant results. One hundred forty four samples had concordant result (96%) whereas six samples showed discordant results (negative with Architect and positive with DiaSorin).Among discordant tests, 5 positive results obtained with DiaSorin were confirmed by Western blot IgG, while one remained indeterminate. More and extensive evaluations may be useful to define Architect sensibility loss, with homogeneous cohorts of patients including those with a syphilis diagnosis, high risk subjects and patients with potential confounding factors like autoimmune diseases.